DIRECT OBSERVATION OF A TETRAHEDRAL BORONIC ACID BETA-LACTAMASE COMPLEX USING B-11 NMR-SPECTROSCOPY - Baldwin, J; Claridge, T; Derome, A; Smith, B; Twyman, M; Waley, S (1991)
A tetrahedral boronic acid-β-lactamase complex formed by treatment of the P99 β-lactamase enzyme from Enterobacter cloacae with 3-dansylamidophenylboronic acid has been directly observed using 11B NMR spectroscopy.